Formulasi dan Uji Aktivitas Antibakteri Streptococcus mutans dari Sediaan Mouthwash Ekstrak Daun Jambu Biji (Psidium guajava L.) - Fitri Handayani; Reksi Sundu; Ria Mareta Sari (Jurnal Sains dan Kesehatan, 2017)
Guava leaves have been used as antidiarrhea, antioxidant, aniinflamation, and antimicrobial. The results of its preliminary phytochemical analysis showed the presence of tannins, flavonoids, steroids and saponins. This leaves also contain essential oil such as sineol. Utilization of guava leaves as a mouthwash preparation is an alternative to replace the mouthwash preparations which generally contain antiseptic form of alcohol that can lead to oral cancer. This experiment formulated the extract of guava leaves into mouthwash that fulfill the physical requirements and determine the differences of antimicrobial activity against the growth of Streptococcus mutans with concentration of extract : 2,5 %; 3% and 3,5 %. Antibacterial acivity test was using MHA media with agar diffusion method. Physical requirement test included organoleptic, pH and viscosity test. The result showed that the mouthwash preparation of guava leaves extract has a pH value outside the range of the optimum growth of bacteria (pH=5). The viscosity of the mouthwash was 1,328-1,347 cP. The antibacterial activity of Streptococcus mutans on F1 has inhibition zone of 3,15 mm, F2 (3,83 mm) and F3 (4,32 mm). It was concluded that the extract of guava leaves on concentrations of 2,5%; 3% and 3,5% can be formulated as mouthwashes. The mouthwash fulfilled the physical requirement test such as pH, viscosity and organoleptic test and can inhibit the growth of Streptococcus mutans.